Max Weber as a Political Economist - Hauke Janssen (Journal of Contextual Economics – Schmollers Jahrbuch, 2020)
Max Weber's path to economic science was impacted to a large degree by political motives. The question emerges how the depiction, which has been maintained by historians of economics, of Weber as a methodologist – who demands objectivity and value freedom in scientific analysis~– is compatible with the view of a young, politically-minded economist who, even from the university lectern, did not shy away from personal value judgments? The manuscripts first published recently in the context of the Max Weber-Gesamtausgabe on his lectures Praktische Nationalökonomie (1895 – 1899) reveal that Weber distinguished sharply between value judgments and scientific analysis – not in order to suppress the former, but in order to be clear about his ultimate goals and its consequences at all times and to elevate these to guide his thinking in practical questions of political economy.
Keywords: N13; P16; P48; Z13; 330; Max Weber; Economic Sociology; Political Economy; Nation